Optimasi Penyerapan Anion Klorida Menggunakan Silika Gel (SiO2) GPTMS Dimodifikasi dengan Dimetilamina - Nur Hafni Hasibuan; Budhi Oktavia; Edi Nasra; Desy Kurniawati (Departemen Kimia FMIPA UNP, 2023)
Ion chloride (Cl-) is an anion that can combine with several cations to form a water-soluble salt. High chloride content in water can accelerate the rusting process on metal. So that in this research the aim is to determine the optimum conditions for the absorption of chloride anions using silica. Adsorption using silica is able to absorb anions. However, modifications are needed to improve silica adsorption. In this study, Dimethylamine was used as a modifier and Glisidoxypropyltrimethoxysilane as a bridge between silica and dimethylamine. To determine the changes in the functional groups of silica, silica-GPTMS, silica-GPTMS DMA, and silica-GPTMS DMA with chloride ions, the FTIR test was carried out. The absorption step was carried out by varying the pH (6,7,8,9, and 10), contact time (30,60,90,120, and 150 minutes), and concentration (5, 10, 15, 20, and 25 mg/L). . The results showed that the optimum conditions for absorption occurred at pH 7, contact time of 120 minutes, and a concentration of 20 mg/L with an absorption capacity of 0.250825 mg/g.